2017
DOI: 10.1002/jcph.890
|View full text |Cite
|
Sign up to set email alerts
|

Antimuscarinic Use in Females With Overactive Bladder Syndrome Increases the Risk of Depressive Disorder: A 3‐Year Follow‐up Study

Abstract: To date, the relationship between antimuscarinics for overactive bladder (OAB) syndrome and depressive disorder still remains unclear. Therefore, this retrospective cohort study examined the association between antimuscarinic use and the subsequent risk of depressive disorder using a population-based data set. This study used data from the Taiwan Longitudinal Health Insurance Database 2005. We selected 1952 OAB women who received antimuscarinics as the study cohort and 9760 OAB women who did not receive antimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 34 publications
2
12
2
Order By: Relevance
“…We did not find that the use of OAB anticholinergic medication was associated with a significant increase in the risk of depression. This is contrary to a previously published study 5 has itself been shown to be associated with depression. 11 Urgency incontinence (usually considered a more severe manifestation of OAB) is more likely to be associated with depression, 12 and women with more severe symptoms are more likely to seek medical treatment.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We did not find that the use of OAB anticholinergic medication was associated with a significant increase in the risk of depression. This is contrary to a previously published study 5 has itself been shown to be associated with depression. 11 Urgency incontinence (usually considered a more severe manifestation of OAB) is more likely to be associated with depression, 12 and women with more severe symptoms are more likely to seek medical treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find that the use of OAB anticholinergic medication was associated with a significant increase in the risk of depression. This is contrary to a previously published study 5 which used administrative data claims to show that women in Taiwan who used anticholinergics for OAB had a significantly increased risk of depression (HR 2.15) compared to women with an OAB diagnosis but no anticholinergic use. A key limitation of that study is that the validity of the codes used to identify untreated OAB patients had not been measured.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Little evidence is available to support the long-term use of anti-muscarinics. Besides the typical systemic effects which can include dry mouth, constipation, and blurry vision, increasing new evidence indicates that cumulative anti-muscarinic use is associated with an increase in incident dementia 18 as well as mood disorders, including depression 19 . These findings support earlier reports of associated depression with short-term anti-muscarinic treatment 20 .…”
Section: Pharmacological Management For Urge Incontinencementioning
confidence: 99%
“…Overactive Bladder (OAB) refers to, according to International Continence Society (ICS) defini-Archives of Psychiatry and Psychotherapy, 2020; 1: [40][41][42][43][44][45][46][47][48] tion from 2002, the occurrence of urinary urgency usually accompanied by pollakiuria (urination 8 or more times a day, or according to recent diagnostic trends such frequency, which is associated with annoyance and a decrease in quality of life) and nokturia (the complaint that the individual has to wake at night one or more times for voiding and urinating is preceded by a period of sleep, which also follows), with a possible urine incontinence [1].…”
Section: Introductionmentioning
confidence: 99%